Writing a series of bestselling research reference books - Chua, Y.P. (University of Toronto Press, 2009)
This author conducted a needs assessment before embarking on the journey of writing a research reference book. The study was carried out to, among other things, identify the topics that the book should cover and determine what readers (561 lecturers at a teacher training institute) would consider a fair asking price for it. Based on the results of this needs assessment, the author wrote a series of books titled Research Method and Statistics, consisting of five volumes totalling fifty-eight chapters and 1677 pages. This five-volume set was published by McGraw-Hill Education Malaysia between 2006 and 2008. Since its publication, the series has been widely used by researchers, educators, and students in local higher educational institutions and is one of McGraw-Hill’s best-selling series. This article describes the needs assessment and details how the results were used as the basis for writing a successful book.